RECEPTION OF YULIAN BACHYNSKYI’S BOOK “UKRAINE IRREDENTA” IN UKRAINIAN NATIONAL MOVEMENT (1894–1900) (Південний архів (історичні науки), 2022)
The purpose of the article is to study reception of the book by Galician political thinker, activist of Ruthenian- Ukrainian Radical Party Yulian Bachynskyi (1870–1940) “Ukraine Irredenta” in Ukrainian national movement at the turn of XIX–XX centuries. The text, which for the first time in history theoretically substantiates the demand for the formation of an independent conciliar state of Ukrainians on both sides of the Zbruch River, appears in the midst of ideological discussions of the last decade of XIX century. The ideological and political conflict of generations in the ranks of the RURP in the first half of 1890s and victory of the Young Radicals faction, whose theorist was Y. Bachynskyi, made possible the further spread of “Ukraine Irredenta” ideas among Ruthenian-Ukrainian intellectuals. The use of discourse research methods such as the analysis of the intellectual context of the publication, reviews of contemporaries, the main points of criticism and reflection of the book in other documents, shows the influence of “Ukraine Irredenta” on modernizing of the political thinking of sub-Austrian Ukrainians. The results of such an approach are a new look at the relations between the currents in the Ukrainian movement of late XIX century, a clearer understanding of the worldview differences between its generations and showing the dynamics of the transition to independentist political culture, which was marked by the struggle and interaction of several ideologies. Conclusions. After conquering the starting point in Radical Party, the idea of creating an independent Ukrainian state, put forward by Bachynskyi in “Ukraine Irredenta”, spread rapidly in the political, social and intellectual space of Galicia, becoming the subject of widespread discussion. In 1899 two new national parties in Habsburg Empire, Ukrainian Social Democratic Party and Ukrainian National Democratic Party, adopted the central thesis of “Ukraine Irredenta” as their own program requirement. The appearance of Y. Bachynskyi’s work (1895) and its resonance should, therefore, be considered not only as a significant event in the intellectual life of Ukrainians in Eastern Galicia, but also as a key link in the process of modernization of Ukrainian national project as a whole.
Keywords: Yulian Bachynskyi, Ivan Franko, Mykhailo Drahomanov, Ruthenian-Ukrainian Radical Party, “Ukraine Irredenta”, Ukrainian socialism, idea of independent state, Ukrainian political thought